Distributive conflict and wage formation in Germany: A Kaleckian perspective on nominal wages and demand (1990-2024) - Houssam Boughabi (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2026)
This paper investigates the interplay between distributive conflict, wage dynamics, and persistent unemployment within a Kaleckian framework, emphasizing the long-memory properties of wages. We develop a stochastic model in which wages adjust adaptively to cumulative historical discrepancies between prices and wages, reflecting backward-looking expectations, institutional rigidities, and distributive conflict. Applying this framework to Germany over the period 1990-2024, we provide empirical evidence that persistent price- wage divergences generate long-lasting effects on real wages and aggregate demand. Within a Kaleckian perspective in which investment and employment are demand-driven, these wage dynamics contribute to the persistence of unemployment by weakening consumption and effective demand over time. Our findings highlight that long-memory wage adjustment amplifies the macroeconomic consequences of distributive conflict and inflation, underscoring the importance of historical wage inertia in shaping employment outcomes. The results offer new insights into the structural origins of persistent unemployment in advanced economies.
Keywords: E12; E24; E32; C22; J30; 330; Kaleckian economics; wage-price dynamics; long-memory; distributive conflict; persistent unemployment